A Software Application to Support Decision-making in Small-scale Photovoltaic Projects - Rigo, Paula Donaduzzi; Rosa, Carmen Brum; Rediske, Graciele; Siluk, Julio Cezar Mairesse; Michels, Leandro (International Journal of Energy Economics and Policy, 2022)
Electricity generation through photovoltaic technology is the fastest growing in the world. Due to its linear power growth characteristic, small-scale generation on grid is common in several countries. In Brazil, in the context of this study, the small-scale solar PV exponentially grows since the implementation of the Distributed Generation market regulation in 2012. Several installer companies have emerged in the country and many residential, commercial and industrial investors are eager to invest in photovoltaic systems. As much as all installers offer the integration of a photovoltaic system, several peculiarities in service and quality are perceived by customers, which makes their decision difficult. So, the aim of this study is to present a software application to support decision-making in small-scale photovoltaic projects. The modelling and application are presented through a case study with an investor who needed to choose between four projects to invest. With the software application use, the investor can reflect on his preferences and changes in the project to improve his satisfaction. Besides, he can compare different projects budgeted by installers, helping in the decision-making process. In the case study, it was possible to see the difference between the four budgets and choose the one that best met the investor’s expectations.